Testing of physical properties and microbial contamination of capsule shell made from starch sago rumbia (Metroxylon sagu Rottb) and carrageenan - Hamlan Ihsan; I Dewa Gede Putra Prabawa; Dwi Harsono; Rinne Nintasari; Rina Apriani; Afandy Bayu Nurcahyo (Kementerian Perindustrian, 2019)
The purpose of this study was to analyse the physical abilities and microbial contamination of modified sago starch using propylene oxide by the hydroxypropylation method. The research design used was a complete randomized design in which the fixed variable was modified propylene oxide sago starch. While the non-permanent variables used sodium tripolyphophate (STPP) at a concentration of 0.3%; 0.5%; 0.6% (b/b) and carrageenan at a concentration of 3%; 2% (b/b). This process was carried out in two stages, adding plasticizers (glycerol) and without plasticizers with a concentration of 2% (v/v). Aquadest used as a solvent with the total amount 100% (b/v). The results of testing he physical properties of the FTIR test process indicate the presence of a spectrum in the region of 3000 - 2500 cm-1 which was a specification of propylene oxide. Whereas for the solubility test of sago starch for water, acid and alike intestinal fluid it met the standards according to Farmakope Indonesia 4th ed. Testing of microbial contamination in pathogenic bacteria types, namely E. coli, Salmonella, and Staphylococcus aureus gave negative test results, whereas for the total plate value (ALT) of sago starch capsules shells showed a value of 1.5x102 cfu/g.